A Longitudinal and Gender Invariance Analysis of the Strengths and Difficulties Questionnaire Across Ages 3, 5, 7, 11, 14, and 17 in a Large U.K.-Representative Sample. (September 2022) - Murray, Aja Louise; Speyer, Lydia Gabriela; Hall, Hildigunnur Anna; Valdebenito, Sara; Hughes, Claire
Developmental invariance is important for making valid inferences about child development from longitudinal data; however, it is rarely tested. We evaluated developmental and gender invariance for one of the most widely used measures of child mental health: the parent-reported Strengths and Difficulties Questionnaire (SDQ). Using data from the large U.K. population-representative Millennium Cohort Study ( N = 10, 207; with data at ages 3, 5, 7, 11, 14, and 17 years), we tested configural, metric, scalar, and residual invariance in emotional problems, conduct problems, hyperactivity/inattention, prosociality, and peer problems. We found that the SDQ showed poor fit at age 3 in both males and females and at age 17 in males; however, it fit reasonably well and its scores were measurement invariant up to the residual level across gender at ages 5, 7, 11, and 14 years. Scores were also longitudinally measurement invariant across this age range up to the partial residual level. Results suggest that the parent-reported SDQ can be used to estimate developmental trajectories of emotional problems, conduct problems, hyperactivity/inattention, prosociality, and peer problems and their gender differences across the age range 5 to 14 years using a latent model. Developmental differences outside of this range may; however, partly reflect measurement differences.